MIMO based Channel Selection Technique for Automation Broadband Networks with IoT Applications - Arulanantham , D.; Palanisamy, C. (International Journal of Psychosocial Rehabilitation, 2019)
The Internet of Things (IoT) alludes to physical and virtual objects that have interesting characters and are associated with the WSN's to encourage applications that make vitality, domestic mechanization, coordination, mechanical control, retail, horticulture, and numerous other spaces "smarter." The Internet of Things could be a modern transformation of the Internet that is quickly gathering force driven by the progressions in sensor systems, versatile gadgets, remote communications, organizing, and cloud innovations. Be that as it may, they must compete for transfer speed with conventional applications such as video spilling, video conferencing, and bulk record exchanges. In the existing system, Active Queue Management (AQM) is being actualized in home gateways, which can ensure IOT streams. Our proposed system is focused on a tremendous volume of information transmission from the server to the client. To attain that, MIMO (Multi Input and Multi Output) technology is actualized in multiplex residential homes. By utilizing this MIMO technology, steady delay and low packet loss can be accomplished.